2013
DOI: 10.4248/br201302002
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 and Phosphate Wasting Disorders

Abstract: A decade ago, only two hormones, parathyroid hormone and 1,25(OH)2D, were widely recognized to directly affect phosphate homeostasis. Since the discovery of fibroblast growth factor 23 (FGF23) in 2000 (1), our understanding of the mechanisms of phosphate homeostasis and of bone mineralization has grown exponentially. FGF23 is the link between intestine, bone, and kidney together in phosphate regulation. However, we still do not know the complex mechanism of phosphate homeostasis and bone mineralization. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 126 publications
0
65
0
5
Order By: Relevance
“…To identify proteins that contributed to phytate-mediated impairment of renal tubular Ca 2+ and phosphate reabsorption, we analyzed the mRNA levels of key renal genes associated with Ca 2+ and phosphate homeostasis, including those associated with Ca 2+ , phosphate channels, and regulatory proteins (Mulay and Anders, 2017; Huang et al, 2013). We found that the renal expression of key genes associated with renal phosphate wasting, including Ca 2+ sensing receptor (CaSR), inositol 1,4,5-trisphosphate receptor 1 (ITPR1), αKlotho, sodium/phosphate cotransporters (NaPi-2a and NaPi-2c), sodium-hydrogen antiporter 3 regulator 1 (NHERF1), and phosphate-regulating neutral endopeptidase X-linked was markedly decreased in phytate-fed rats ( figure supplement 7A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify proteins that contributed to phytate-mediated impairment of renal tubular Ca 2+ and phosphate reabsorption, we analyzed the mRNA levels of key renal genes associated with Ca 2+ and phosphate homeostasis, including those associated with Ca 2+ , phosphate channels, and regulatory proteins (Mulay and Anders, 2017; Huang et al, 2013). We found that the renal expression of key genes associated with renal phosphate wasting, including Ca 2+ sensing receptor (CaSR), inositol 1,4,5-trisphosphate receptor 1 (ITPR1), αKlotho, sodium/phosphate cotransporters (NaPi-2a and NaPi-2c), sodium-hydrogen antiporter 3 regulator 1 (NHERF1), and phosphate-regulating neutral endopeptidase X-linked was markedly decreased in phytate-fed rats ( figure supplement 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the renal expression of key genes associated with renal phosphate wasting, including Ca 2+ sensing receptor (CaSR), inositol 1,4,5-trisphosphate receptor 1 (ITPR1), αKlotho, sodium/phosphate cotransporters (NaPi-2a and NaPi-2c), sodium-hydrogen antiporter 3 regulator 1 (NHERF1), and phosphate-regulating neutral endopeptidase X-linked was markedly decreased in phytate-fed rats ( figure supplement 7A ). Each of these genes is associated with the development of nephrocalcinosis and renal phosphate wasting (Shavit et al, 2015; Huang et al, 2013; Karim et al, 2008; Monico and Milliner, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Definition ARHR is another rare hereditary renal phosphate wasting disorder characterized by hypophosphatemia, rickets, and/or osteomalacia and slow growth [32,52].…”
Section: Autosomal Recessive Hypophosphatemic Ricketsmentioning
confidence: 99%
“…The excessive increase of plasma FGF23 concentrations, compromized 1,25(OH) 2 D 3 formation and renal phosphate wasting in patients carrying loss of function mutations of PHEX [20,22]) interferes with bone mineralization leading to several clinical disorders including limb deformity, short stature, arthritis, enthesopathy, hearing impairment, optic atrophy and nephrocalcinosis [21][22][23][24]. Loss of function mutations of DMP-1 lead to rickets/ osteomalacia later during childhood or in adulthood [23].…”
Section: Clinical Significance Of Fgf23 Excessmentioning
confidence: 99%
“…Loss of function mutations of DMP-1 lead to rickets/ osteomalacia later during childhood or in adulthood [23].…”
Section: Clinical Significance Of Fgf23 Excessmentioning
confidence: 99%